The Relationship between Motion and Time in the Philosophy of Avicenna and Mulla Sadra - Asef ehsani (حکمت اسرا)
The question of this paper is the relationship between motion and time. Though philosophical debates are intrinsically difficult, the entanglement of the two concepts of motion and time, and the fact that they are mixed with nothingness, add to the complexity of this relationship and has put it in a hollow of ambiguity. In the discussion of motion, Avicenna, by denying the existence of the external existence of the definite motion, defends the mediated motion as the external reality of motion. But Mulla Sadra, according to his theory of substantial motion, argues for the objectivity of the definite motion. Avicenna considers the time, following the motion, of the accidentals of the body, so he presents it in the physics. But Mulla Sadra regards time as the amount of motion in the substance, that is, the universe is constantly in motion, change and regeneration, and time is the amount of this regeneration and change in the nature. Sadra considers time as the predicate of analytical accidental and a philosophical secondary concept. For Avicenna, time never corresponds with the mediated motion, as the external reality of motion; instead it corresponds with the regenerative and discontinuous proportions of the uniform motion of the heavens. But, according to Sadra, the definite motion, as the objective truth of motion, is the very regeneration and elapsing, and it has a total correspondence with time.